Computer based motor control through universal serial bus (USB) - 249257 Chan, Yei Yang (Skudai : Universiti Teknologi Malaysia, 2000)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 2000